Impact of Corrosive Trace Elements on Sea Turtle Eggs during Embryonic Growth - GOKSEL OZDILEK, HASAN; YALCIN OZDILEK, SUKRAN (Asian Journal of Chemistry, 2010)
In the present work, the authors have tried to define harmful elements in the sand that cause unsuccessful hatchlings. These elements are most probably in the untreated domestic wastewater that is discharged by tanker trucks nearby densely nested locations.